1998
DOI: 10.1007/s002340050651
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal angioplasty for intracranial arteriosclerotic lesions

Abstract: We report 17 cases of intracranial arterial stenosis treated by percutaneous transluminal angioplasty (PTA), including 9 on the intracranial internal carotid (ICA), 4 on the middle cerebral (MCA), and 4 on vertebrobasilar artery (VBA) system. All patients had ischaemic brain symptoms and stenoses of more than 60% (calculated angiographically). We treated four patients by PTA for residual stenoses after thrombolysis for acute occlusion. We used PTA balloon catheters 2.0-3.5 mm in diameter for all procedures. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Reported target ACT ranges have varied from 150 -200 seconds to 350 -400 seconds. [50][51][52][53] Data regarding the optimal ACT for neuroendovascular procedures are scant because testing methods and ACT goal ranges are not commonly reported. Most of the evidence available is based on experts' opinion and/or extrapolated from PCI literature.…”
Section: Optimal Act For Neuroendovascular Proceduresmentioning
confidence: 99%
“…Reported target ACT ranges have varied from 150 -200 seconds to 350 -400 seconds. [50][51][52][53] Data regarding the optimal ACT for neuroendovascular procedures are scant because testing methods and ACT goal ranges are not commonly reported. Most of the evidence available is based on experts' opinion and/or extrapolated from PCI literature.…”
Section: Optimal Act For Neuroendovascular Proceduresmentioning
confidence: 99%
“…The postangioplasty stenosis grade defining technical success varies from Յ20% residual stenosis, 70 Յ30% residual stenosis, 96 but most commonly Յ50% residual stenosis. 2,54,58,60,68,94,119 Most importantly, technical success should be heralded by freedom from ipsilateral ischemic or hemorrhagic strokes in the distribution of the treated target stenosis.…”
Section: Anatomic Outcome Technical Successmentioning
confidence: 99%
“…A nonrandomized case series suggested that VAS may be treated using an endovascular method such as PTA and/or stenting and is associated with low morbidity and mortality [14][15][16] . However, results of PTA performed to relieve stenosis in the posterior intracranial circulation have been conflicting [17][18][19] . Thus, we conducted a prospective study to evaluate the efficacy, safety, and long-term follow-up of 206 patients who received PTA with a stent implant to treat their symptomatic atherosclerotic VAS.…”
Section: Introductionmentioning
confidence: 99%